DNA Damage Modulates Nucleolar Interaction of the Werner Protein with the AAA ATPase p97/VCP - Partridge, Juneth Joaquin (The American Society for Cell Biology, 2003)
We report a novel nucleolar interaction between the AAA ATPase p97/VCP and the Werner protein (WRNp), a member of the RecQ helicase family. p97/VCP mediates several important cellular functions in eucaryotic cells, including membrane fusion of the endoplasmic reticulum and Golgi and ubiquitin-dependent protein degradation. Mutations in the WRN gene cause Werner syndrome, a genetic disorder characterized by premature onset of aging symptoms, a higher incidence of cancer, and a high susceptibility to DNA damage caused by topoisomerase inhibitors. We observed that both WRNp and valosin-containing protein (VCP) were present in the nucleoplasm and in nucleolar foci in mammalian cells and that WRNp and p97/VCP physically interacted in the nucleoli. Importantly, the nucleolar WRNp/VCP complex was dissociated by treatment with camptothecin, an inhibitor of topoisomerase I, whereas other WRNp-associated protein complexes, such as WRNp/Ku 80, were not dissociated by this drug. Because WRN syndrome cells are sensitive to topoisomerase inhibitors, these observations suggest that the VCP/WRNp interaction plays an important role in WRN biology. We propose a novel role for VCP in the DNA damage response pathway through modulation of WRNp availability.